Huangqi Guizhi Wuwu decoction alleviates oxaliplatin-induced peripheral neuropathy via the gut-peripheral nerve axis - Zhengwei Zhang; Juan Ye; Xinyu Liu; Wenjing Zhao; Bing Zhao; Xuejiao Gao; Hongli Lan; Yuze Wu; Yang Yang; Peng Cao (BMC, 2023)
Abstract Background Oxaliplatin-induced peripheral neurotoxicity (OIPN) limits the dose of chemotherapy and seriously affects the quality of life. Huangqi Guizhi Wuwu Decoction (HGWD) is a classical Traditional Chinese Medicine (TCM) formula for the prevention of OIPN. However, its specific pharmacological mechanism of action remains unknown. Our study found that HGWD can effectively alleviate chronic OIPN and regulate intestinal flora. Therefore, we explored the mechanism of action of HGWD in alleviating chronic OIPN from the perspective of intestinal flora. Methods In this study, we established an OIPN model in C57BL/6 mice treated with different concentrations of HGWD. Mechanical pain and cold pain were assessed at certain time points, and samples of mice colon, dorsal root ganglion (DRG), serum, and feces were collected. Associated inflammation levels in the colon and DRG were detected using immunohistochemical techniques; the serum lipopolysaccharide (LPS) levels and associated inflammation were assessed using the appropriate kits; and 16S rRNA sequencing was used to examine the dynamic changes in gut microorganisms. Finally, established fecal microbiota transplantation (FMT) and antibiotic (ABX) pretreatment models were used to validate flora's role in HGWD for chronic OIPN by pain scoring and related pathological analysis. Results HGWD treatment significantly alleviated pain sensitivity in chronic OIPN mice. Pathological results showed that HGWD treatment improved intestinal ZO-1 expression and reduced serum LPS levels and associated inflammatory factors in the colon, serum, and DRG. The 16S rRNA results showed that HGWD restored the composition of the intestinal flora in a time-dependent manner to alleviate OIPN. FMT and ABX experiments demonstrated that HGWD can alleviate chronic OIPN by regulating intestinal flora homeostasis. Conclusions HGWD prevents chronic OIPN by dynamically regulating intestinal flora homeostasis, thereby ameliorating intestinal barrier damage and reducing serum LPS and relevant inflammatory factor levels in the colon, serum, and DRG.